Microwave-assisted efficient one-pot synthesis of N2-(tetrazol-5-yl)-6-aryl/heteroaryl-5,6-dihydro-1,3,5-triazine-2,4-diamines - Moustafa, Moustafa Sherief; Mekheimer, Ramadan Ahmed; Al-Mousawi, Saleh Mohammed; Abd-Elmonem, Mohamed; El-Zorba, Hesham; Hameed, Afaf Mohamed Abdel; Mohamed, Tahany Mahmoud; Sadek, Kamal Usef (Beilstein Journal of Organic Chemistry, 2020)
An efficient one-pot synthesis of N2-(tetrazol-5-yl)-6-aryl/heteroaryl-1,3,5-triazine-2,4-diamine derivatives was developed by reacting 5-amino-1,2,3,4-tetrazole with aromatic aldehydes and cyanamide in pyridine under controlled microwave heating with high yields. X-ray crystallography confirmed the structure of the obtained products.
Keywords: microwave irradiation; N2-(tetrazol-5-yl)-6-aryl/heteroaryl-1,3,5-triazine-2,4-diamines; one-pot synthesis; X-ray crystallography

(untitled) - Nishigaki, S.; Yoneda, F.; Matsumoto, H.; Morinaga, K. (J. Med. Chem., 1969)

(untitled) - Goda, F.; Tantawy, A.; Abouzeid, L.; Badr, S.; Selim, K. (Saudi Pharm. J., 2008)

(untitled) - Sączewski, F.; Bułakowska, A.; Bednarski, P.; Grunert, R. (Eur. J. Med. Chem., 2006)

(untitled) - Chen, X.; Zhan, P.; Liu, X.; Cheng, Z.; Meng, C.; Shao, S.; Pannecouque, C.; Clercq, E. D.; Liu, X. (Bioorg. Med. Chem., 2012)

(untitled) - Landi, G.; Linciano, P.; Borsari, C.; Bertolacini, C. P.; Moraes, C. B.; Cordeiro-da-Silva, A.; Gul, S.; Witt, G.; Kuzikov, M.; Costi, M. P.; Pozzi, C.; Mangani, S. (ACS Infect. Dis., 2019)

(untitled) - Poirier, M.; Awale, M.; Roelli, M. A.; Giuffredi, G. T.; Ruddigkeit, L.; Evensen, L.; Stooss, A.; Calarco, S.; Lorens, J. B.; Charles, R.-P.; Reymond, J.-L. (ChemMedChem, 2019)

(untitled) - Lourens, A. C. U.; Gravestock, D.; van Zyl, R. L.; Hoppe, H. C.; Kolesnikova, N.; Taweechai, S.; Yuthavong, Y.; Kamchonwongpaisan, S.; Rousseau, A. L. (Org. Biomol. Chem., 2016)

(untitled) - Ma, X.; Tan, S.-T.; Khoo, C.-L.; Sim, H.-M.; Chan, L.-W.; Chui, W.-K. (Bioorg. Med. Chem. Lett., 2011)

(untitled) - Hanessian, S.; Sgarbi, P. W. M. (Bioorg. Med. Chem. Lett., 2000)

(untitled) - Hajduk, P. J.; Dinges, J.; Schkeryantz, J. M.; Janowick, D.; Kaminski, M.; Tufano, M.; Augeri, D. J.; Petros, A.; Nienaber, V.; Zhong, P.; Hammond, R.; Coen, M.; et al. (J. Med. Chem., 1999)

(untitled) - Kosáry, J.; Kasztreiner, E.; Rablóczky, G.; Kürthy, M. (Eur. J. Med. Chem., 1989)

Progress in Drug Research - Burger, A. (Isosterism and bioisosterism in drug design, 2011)

(untitled) - Ostrovskii, V. A.; Trifonov, R. E.; Popova, E. A. (Russ. Chem. Bull., 2012)

(untitled) - Malik, M. A.; Al-Thabaiti, S. A.; Malik, M. A. (Int. J. Mol. Sci., 2012)

(untitled) - Muralikrishna, S.; Raveendrareddy, P.; Ravindranath, L. K.; Harikrishna, S.; Pathange, J. (Der Pharm. Chem., 2013)

(untitled) - Ostrovskii, V. A.; Koren, A. O. (Heterocycles, 2000)

(untitled) - Mohite, P. B.; Bhaskar, V. H. (Int. J. PharmTech Res., 2011)

(untitled) - Adamec, J.; Waisser, K.; Kuneš, J.; Kaustová, J. (Arch. Pharm. (Weinheim, Ger.), 2005)

(untitled) - Bachar, S. C.; Lahiri, S. C. (Pharmazie, 2004)

Design of Hybrid Molecules for Drug Development - Decker, M. (Elsevier, 2017)

(untitled) - Shaveta; Mishra, S.; Singh, P. (Eur. J. Med. Chem., 2016)

(untitled) - Solomon, V. R.; Hu, C.; Lee, H. (Bioorg. Med. Chem., 2009)

(untitled) - Kelly, P. M.; Keely, N. O.; Bright, S. A.; Yassin, B.; Ana, G.; Fayne, D.; Zisterer, D. M.; Meegan, M. J. (Molecules, 2017)

(untitled) - Pingaew, R.; Saekee, A.; Mandi, P.; Nantasenamat, C.; Prachayasittikul, S.; Ruchirawat, S.; Prachayasittikul, V. (Eur. J. Med. Chem., 2014)

(untitled) - Pitts, W. J.; Guo, J.; Dhar, T. G. M.; Shen, Z.; Gu, H. H.; Watterson, S. H.; Bednarz, M. S.; Chen, B.-C.; Barrish, J. C.; Bassolino, D.; Cheney, D.; Fleener, C. A.; et al. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Hirt, R.; Nidecker, H.; Berchtold, R.; Schönholzer, G. (Helv. Chim. Acta, 1950)

(untitled) - List, M.; Puchinger, H.; Gabriel, H.; Monkowius, U.; Schwarzinger, C. (J. Org. Chem., 2016)

(untitled) - Alkalay, D.; Volk, J.; Bartlett, M. F. (J. Pharm. Sci., 1976)

(untitled) - Yuki, Y.; Sakurai, S.; Kakurai, T.; Noguchi, T. (Bull. Chem. Soc. Jpn., 1970)

(untitled) - Shapiro, S. L.; Isaacs, E. S.; Parrino, V. A.; Freedman, L. (J. Org. Chem., 1961)

(untitled) - Irikura, T.; Abe, Y.; Okamura, K.; Higo, K.; Maeda, A.; Morinaga, F.; Shirai, G.; Hatae, S. (J. Med. Chem., 1970)

(untitled) - Liu, C.; Lin, J.; Leftheris, K. (Tetrahedron Lett., 2007)

(untitled) - Ma, X.; Poon, T.-Y.; Wong, P. T. H.; Chui, W.-K. (Bioorg. Med. Chem. Lett., 2009)

(untitled) - Carpenter, R. D.; Lam, K. S.; Kurth, M. J. (J. Org. Chem., 2007)

(untitled) - Caddick, S. (Tetrahedron, 1995)

(untitled) - Hameed, A. A.; Ahmed, E. K.; Fattah, A. A. A.; Andrade, C. K. Z.; Sadek, K. U. (Res. Chem. Intermed., 2017)

(untitled) - Sadek, K. U.; Mekheimer, R. A.; Mohamed, T. M.; Moustafa, M. S.; Elnagdi, M. H. (Beilstein J. Org. Chem., 2012)

Microwave Synthesis: Chemistry at the Speed of Light - Hayes, B. L. (CEM Publishing, 2002)

(untitled) - Kaval, N.; Ermolat'ev, D.; Appukkuttan, P.; Dehaen, W.; Kappe, C. O.; Van der Eycken, E. (J. Comb. Chem., 2005)

(untitled) - Nüchter, M.; Ondruschka, B.; Bonrath, W.; Gum, A. (Green Chem., 2004)

(untitled) - Abdel Hameed, A. M.; Moustafa, M. S.; Al-Mousawi, S. M.; Awed, R. R.; Sadek, K. U. (Green Process. Synth., 2017)

(untitled) - Mekheimer, R. A.; Hameed, A. A.; Sadek, K. U. (Green Chem., 2008)

(untitled) - Dyab, A. K. F.; Sadek, K. U. (RSC Adv., 2018)

(untitled) - Abdel Hamid, A.; Abd-Elmonem, M.; Hayallah, A. M.; Abo Elsoud, F. A.; Sadek, K. U. (ChemistrySelect, 2017)

Comprehensive Heterocyclic Chemistry III - Ostrovskii, V. A.; Koldobskii, G. I.; Trifonov, R. E. (Tetrazoles, 2008)